Editorial: is pharmacogenetic testing for adverse effects to IBD treatments ready for roll‐out?. Issue 6 (28th August 2020) - Chee, Desmond; Goodhand, James R.; Ahmad, Tariq
Abstract : LINKED CONTENT This article is linked to Bangma et al paper. To view this article, visit https://doi.org/10.1111/apt.15762